PENGARUH FAKTOR BAURAN PEMASARAN TERHADAP KEPUTUSAN NASABAH DALAM MEMILIH JASA BANK JATENG CABANG KENDAL (Students' Journal of Economic and Management, 2013)
This study discusses the influence of marketing mix factors against the decision of the customer in choosing the services of Bank Jateng branch of Kendal. As for the marketing mix is comprised of product, price, place, promotion, human resources, physical infrastructure, and processes.The number of samples used in the study of 100 respondents. Determination of the sample using a purposive sampling method with a minimum of three times for a visit to the Central Java branch of the Bank's minimum age of Kendal, respondents 17 years and respondents are not employees of the Bank branch And Kendal. In this study using data processing applications SPSS (Statistical Package for Social Sciences). Data analysis includes qualitative and quantitative analysis. The qualitative analysis of the interpretation of the data obtained in the study with give a description and explanation on the results of the data processing has been done. While the quantitative analysis includes tests of validity and reliability, classic assumption test, multiple regression analysis, analysis of the coefficient of determination (R2), test the hypothesis test and t-test through the F. The result is product, place, promotion, human resources, and physical infrastructure,variables are positive and significant effect against the decision of the customer in choosing the services of Bank Jateng branch Kendal, while the variable rates and processes the influential variables are positive and insignificant against the decision of the customer in choosing the services of Bank Jateng branch of Kendal. Results of the study also showed that the marketing mix factors are tested simultaneously in a positive and significant effect against the decision of the customer in choosing the services of Bank Jateng branch of Kendal. Keywords: product, price, place, promotion, physical evidence, human resources, processes, and decisions of the customer